Transgenderities in Performance: gender disobedience and anticoloniality in the performing arts - Leal, Dodi; Rosa, André (Revista Brasileira de Estudos da Presença, 2020)
The article presents the scenic devices of transgender performativity in face of the practical and theoretical paths of anticolonial rupture of body norms. It is questioned here the extent to which gender disobedience is an essential factor in the struggle against the colonial project, highlighting how Eurocentrism and whiteness are amalgamated with the precepts of compulsory cisgenderity as body politics. Two performances are analyzed: Tetagrafias and Tran(S)arau (Coimbra/Portugal, 2015 to 2017). Therefore, the coercive aspects of cisnormativity are presented as hegemonic and colonial conception of corporeality, in scene and in daily life.